Prohibition Questions and Answers - Ministry of Information and Broadcasting (Ministry of Information and Broadcasting, 1956)
India’s prohibition policy, rooted in the Indian National Congress’s pre-independence commitment under Mahatma Gandhi, sought to curb alcohol consumption as a moral, social, and public health imperative. Legislative efforts began in 1937, with provinces like Bombay, Madras, and Uttar Pradesh implementing bans, and continued post-independence with total prohibition in select regions. The policy aimed to reduce alcohol-related societal harm, improve public health, and align with constitutional mandates on health and welfare, while addressing economic, employment, and cultural concerns. Key considerations included balancing individual liberty with societal good, mitigating revenue loss through alternative means, offering employment alternatives for affected workers, and accommodating religious practices. Advocates argued that despite implementation challenges, prohibition promotes societal productivity, strengthens moral values, and enhances overall public welfare, reflecting India’s commitment to health and ethical governance.
The Publications Division - Ministry of Information and Broadcasting Government of India
Keywords: Prohibition Policy; Indian National Congress; Mahatma Gandhi; Alcohol Ban; Public Health; Legislative Initiatives; Economic Impact; Moral Considerations; Employment Alternatives; Opium Prohibition; Social Welfare; Cultural Practices